Analisis Kelayakan Bisnis Pada Usaha Laundry Express Antar Jemput - Irma Erviana Sari; Novi Lisdayanti; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The changing lifestyle of urban communities has led to an increasing demand for practical services, including express laundry with pick-up and delivery services. This study aims to analyze the business feasibility of an express laundry service with pick-up and delivery. The analysis considers market, technical, management, legal, and financial aspects to determine whether the business is viable. The research method involves market surveys, in-depth interviews, and financial feasibility analysis using parameters such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). The results indicate that the express laundry business with pick-up and delivery services has a large market potential with high consumer interest. From a financial perspective, this business demonstrates profitability that meets investment criteria, while the main challenges lie in logistics management and the development of effective marketing strategies.